Atogepant: an emerging treatment for migraine. (13th April 2022) - Rustichelli, Cecilia; Avallone, Rossella; Ferrari, Anna
ABSTRACT: Introduction: Until recently, only nonspecific and not always well-tolerated medications were available for migraine prophylaxis. Currently, specific drugs such as calcitonin gene-related peptide (CGRP) monoclonal antibodies and second-generation gepants are marketed for migraine treatment. Atogepant, an orally active small molecule, is a potent, selective antagonist of the CGRP receptor and is the only gepant authorized exclusively for episodic migraine prophylaxis in adults. Areas covered: Using literature obtained from PubMed, Scopus, Web of Science, Cochrane, and ClinicalTrials.gov (up to February 13 rd, 2022), the authors summarize and evaluate the available data on atogepant for the prophylaxis of episodic migraine. Expert opinion: From pivotal trials, the efficacy and tolerability of atogepant in episodic migraine prophylaxis seem comparable to those of CGRP monoclonal antibodies, even if comparative studies have not been conducted. To date, limited information is available on atogepant, including the optimal dose and duration of therapy; hence, it is difficult to establish whether it could be a first-line drug for migraine prophylaxis. Furthermore, it is important to evaluate if atogepant use is associated with the risk of cardiovascular and cerebrovascular events, which could result from potent and persistent blockade of vasodilation by CGRP.